Bioinformatics and Drug Discovery - Larson, Richard S; Ed (Humana Press, 2006)
A collection of reproducible bioinformatic methods to advance the drug discovery process from gene identification to protein modeling to the identification of specific drug candidates. It demonstrates these techniques, including microarray analysis, the analysis of genes as potential drug targets and virtual screening and in silico protein design.